Cry wolf - predicted costs by industry in the face of new regulations (Göteborg, 2004)
"Industry has for years overestimated the cost of implementing environmental legislation in order to persuade politicians to weaken or drop proposed environmental law according to ‘Cry Wolf’. 'Cry Wolf' outlines five case studies: EC Directive on vehicle emissions standards European auto-oil programme; UN/EC protocols on acidifcation; US Clean Air Act; and the Montreal Protocol on ozone layer depleting substances. Each case study shows vastly overestimated costs and impacts predicted by industry during the legislative debate, and demonstrates that final results fall a very long way short of the catastrophic outcomes predicted by industry. The report appeals to politicians not fall for industry overestimates in the current debate about EU chemical reform: "It is vital that politicians realise that REACH will not be the burden it has been predicted to be" and states "the benefits of REACH far outweigh its implementation costs." "